Measuring PAGI Values in Student Character Development: A Quantitative Study of Universitas PGRI Adi Buana Surabaya - Ayong Lianawati; Budi Purwoko; Muwakhidah Muwakhidah; Ananda Dea Saputri (Journal of Education and Counseling (JECO), 2025)
This study aims to measure the level of internalization of PAGI character values (Caring, Trustworthy, Persistent, and Innovative) among students at Universitas PGRI Adi Buana Surabaya and to identify implementation challenges in the digital era. Using a descriptive quantitative approach, this research involved a survey of 524 students selected through random sampling. The research instrument was a questionnaire with 76 statement items that was tested for validity and reliability, yielding a Cronbach's Alpha value of 0.960. The results show that the majority of students (76.13%) are in the "moderate" category for PAGI character internalization, while 12.35% are in the "high" category and 11.52% are in the "low" category. This finding indicates that although the PAGI character-building program has progressed well, further strengthening is still necessary. Deeper analysis reveals specific challenges, such as the influence of digital culture hindering the 'Caring' character, and passive learning patterns limiting the development of the 'Innovative' character. The 'Persistent' character was also identified as a significant weakness, with students' motivation to persevere when faced with failure remaining relatively low. This study concludes that a more intensive and integrated strategy for strengthening and socialization is required to deeply instill PAGI values and recommends a contextual approach that integrates these values into all aspects of campus life to produce graduates who are not only academically superior but also possess strong, adaptive characters to face future challenges.